Bright Luminal Sign on High b-Value Diffusion-Weighted Magnetic Resonance Enterography Imaging as a New Biomarker to Predict Fibrotic Strictures in Crohn’s Disease Patients: A Retrospective Preliminary Study - Luca Pio Stoppino; Stefano Piscone; Ottavia Quarta Colosso; Sara Saccone; Paola Milillo; Nicola Della Valle; Rodolfo Sacco; Alfonso Reginelli; Luca Macarini; Roberta Vinci (Journal of Imaging)
A retrospective analysis was conducted to investigate how a bright luminal sign on high b-value diffusion-weighted imaging (DWI) could be considered as a new biomarker for identifying fibrotic strictures in Crohn’s disease (CD). Fibrotic strictures, due to excessive deposition of extracellular matrix following chronic inflammatory processes, can be difficult to distinguish from inflammatory strictures using endoscopy. This study was performed on 65 patients with CD who underwent MRE, and among them 32 patients showed the bright luminal sign on high b-value DWI. DWI findings were compared to pre- and post-contrast MRE data. Luminal bright sign performance results were calculated using a confusion matrix, the relationship between categorical variables was assessed by the χ2 test of independence, and the Kruskal–Wallis test (ANOVA) was used for the assessment of statistical significance of differences between groups. The results indicated a high sensitivity (90%) and specificity (85%) of the bright luminal sign for fibro-stenotic CD and a significant correlation between DWI luminal brightness and markers such as the homogeneous enhancement pattern (p < 0.001), increase in enhancement percentage from 70 s to 7 min after gadolinium injection (p < 0.001), and submucosal fat penetration (p = 0.05). These findings indicate that DWI hyperintensity can be considered as a good non-invasive indicator for the detection of severe intestinal fibrosis and may provide an efficient and accurate method for assessing fibrotic strictures. This new non-invasive biomarker could allow an early diagnosis of fibrotic stricture, delaying the onset of complications and subsequent surgery. Moreover, further evaluations through larger prospective trials with histopathological correlation are needed to confirm these results and completely determine the clinical benefits of DWI in treating CD.